2019
DOI: 10.4039/tce.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on instar number and larval development in the endangered longhorn beetle Callipogon relictus (Coleoptera: Cerambycidae) raised on an artificial diet

Abstract: Callipogon relictus Semenov (Coleoptera: Cerambycidae) is currently listed in the Red Data Books (Category I) of Russia and South Korea and, in 2006, was designated by the South Korean government as the first invertebrate priority target species in a restoration project. However, the species is also classified as an invasive quarantine pest by the Canadian Food Inspection Agency. Due to the five-year to seven-year life cycle of the species, experimental information about instar numbers has been poorly document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It was also reported that the ancestors of C. relictus were not northern or boreal species but rather adapted to the climate of Northeast Asia [4]. Recently, experimental evidence that higher temperatures both accelerate larval development and increase body size was reported [82,87]. An alternative hypothesis for the local extinction or dramatic population decreases of C. relictus in South Korea is that the rapid reduction in population was caused by anthropogenic habitat destruction rather than climate change.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that the ancestors of C. relictus were not northern or boreal species but rather adapted to the climate of Northeast Asia [4]. Recently, experimental evidence that higher temperatures both accelerate larval development and increase body size was reported [82,87]. An alternative hypothesis for the local extinction or dramatic population decreases of C. relictus in South Korea is that the rapid reduction in population was caused by anthropogenic habitat destruction rather than climate change.…”
Section: Discussionmentioning
confidence: 99%
“…This variability in larvae instar development time may be determined by environmental factors (temperature, humidity, and oxygen levels) and nutritional conditions. Temperature affected the development time of immature stages of Ips typographus L. (Coleoptera: Scolytinae), Callipogon relictus Semenov (Coleoptera: Cerambycidae), and Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae) (Keena and Moore 2010;Štefková et al 2017;Yi et al 2019). Li et al (2015) also reported that the development of Bradysia odoriphaga (Diptera: Sciaridae) at 15°C was slower than that at 20, 25, and 30°C in the laboratory.…”
Section: Biological Characteristics Of D Frumentimentioning
confidence: 99%
“…Inaccessibility makes deciphering the number of larval instars for any woodborer under natural conditions difficult. It is, therefore, common to rear these insects on artificial diet for instar determination (Yi et al 2019), something beyond the scope of this study.…”
Section: Larval Developmentmentioning
confidence: 99%